The association between HL. A class II and iraqi leukemic patients. - Zeiny, Sarmad M.; Al-Ani, Mohammed M.; Alwahed, Laith Abid (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Leukemia isba type of cancer of the blood or bone marrow that is characterized by an abnormal increase of white blood cells.